Effect of a backboard on chest compression quality during in-hospital adult cardiopulmonary resuscitation: A randomised, single-blind, controlled trial using a manikin model. (April 2022) - Cuvelier, Zara; Houthoofdt, Ruben; Serraes, Brecht; Haentjens, Carl; Blot, Stijn; Mpotos, Nicolas
Abstract: Introduction: Chest compression quality during in-hospital resuscitation is often suboptimal on a soft surface. Scientific evidence regarding the effectiveness of a backboard is scarce. This single-blinded manikin study evaluated the effect of a backboard on compression depth, rate and chest recoil performed by nurses. Sex, BMI, age and clinical department were considered as potential predictors. Methods: Using self-learning, nurses were retrained to achieve a minimal combined compression score at baseline. This combined score consisted of ≥70% compressions with depth 50–60 mm, ≥70% compressions with complete release (≤5mm) and a mean compression rate of 100–120 bpm. Subsequently, nurses were allocated to a backboard or control group and performed a two-minute cardiopulmonary resuscitation test. The main outcome measure was the difference in proportion of participants achieving a combined compression score of ≥70%. Results: In total 278 nurses were retrained, 158 nurses dropped out and 120 were allocated to the backboard (n = 61) or control group (n = 59). The proportion of participants achieving a combined compression score of ≥70% was not significantly different (p = 0.475) and suboptimal in both groups: backboard group 47.5% (backboard) versus 41.0% (control). Older age (≥51 years) was associated with a lower probability of achieving a combined compression score >70% [OR = 0.133; 95% confidence interval (CI), 0.037–0.479; p = 0.002]. Conclusion: Using a backboard did not significantly improve compression quality in our study. Important decay of compression skills was observed in both groups, highlighting the importance of frequent retraining, particularly in some age groups.